A mini-review: Advances in plant-derived extracellular vesicles as nano-delivery systems for tumour therapy - Zhu, Ying; Zhou, Xiaona; Yao, Zheng (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract Extracellular vesicles are functionally active, nanoscale, membrane-bound vesicles that can be secreted by all cells. They have a key role in most health and disease states and have gradually become a promising class of delivery vehicles for targeted therapies for a variety of diseases. Plant-derived extracellular vesicles have received increasing attention based on their easy availability, non-toxicity and high absorption. However, compared with mammalian extracellular vesicles, the role of these nanoparticles as nano-delivery systems in tumour therapy has been underestimated. In this paper, the application of plant-derived extracellular vesicles and their nano-derivatives as nano-delivery systems in tumour therapy is reviewed to illustrate their great application potential.